Design and analysis of a compact four-port MIMO antenna with enhanced isolation for UWB application - Al Gburi, Ahmed Jamal Abdullah; Koteswara Rao Devana, Venkata Naga; Sarita, Vanka; Dhineshbabu, Nattanmai Raman; G. S.K., Gayatri Devi; Lavuri, Nageswara Rao; Praveenkumar, Seepana; Abduljaleel, Hala Kamal (Intelligent Network and Systems Society, 2025)
A compact four-port self-isolated multiple-input multiple-output (MIMO) antenna with enhanced isolation for ultrawideband (UWB) and X-band applications is presented. The proposed antenna is printed on an FR-4 substrate with a size of 35 × 35 mm² and features embedded elliptical, circular, and rectangular structures as the radiating patch, along with a semi-elliptical defected ground structure (SE-DGS). The antenna operates over a frequency range of 3.91 GHz to beyond 15 GHz, achieving a peak gain of 5.41 dBi, a peak radiation efficiency of 92.84%, and an isolation of more than 30 dB across the operating band for UWB and X-band applications. The diversity characteristics include an envelope correlation coefficient (ECC) of less than 0.001, a diversity gain (DG) exceeding 9.99 dB, and a mean effective gain (MEG) lower than -3.01 dB, all achieved without the need for additional coupling elements among the antenna elements. The simulated results of the proposed antenna show a strong correlation with the measured results, making it a promising candidate for UWB-MIMO applications.